Metabolic syndrome, metabolic comorbid conditions and risk of early-onset colorectal cancer. Issue 6 (9th October 2020) - Chen, Hanyu; Zheng, Xiaobin; Zong, Xiaoyu; Li, Zitong; Li, Na; Hur, Jinhee; Fritz, Cassandra DL; Chapman Jr, William; Nickel, Katelin B; Tipping, Andrew; Colditz, Graham A; Giovannucci, Edward L; et al.
Abstract : Objective: Factors that lead to metabolic dysregulation are associated with increased risk of early-onset colorectal cancer (CRC diagnosed under age 50). However, the association between metabolic syndrome (MetS) and early-onset CRC remains unexamined. Design: We conducted a nested case–control study among participants aged 18–64 in the IBM MarketScan Commercial Database (2006–2015). Incident CRC was identified using pathologist-coded International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes, and controls were frequency matched. MetS was defined as presence of ≥3 conditions among obesity, hypertension, hyperlipidaemia and hyperglycaemia/type 2 diabetes, based on ICD-9-CM and use of medications. Multivariable logistic regressions were used to estimate ORs and 95% CIs. Results: MetS was associated with increased risk of early-onset CRC (n=4673; multivariable adjusted OR 1.25; 95% CI 1.09 to 1.43), similar to CRC diagnosed at age 50–64 (n=14 928; OR 1.21; 95% CI 1.15 to 1.27). Compared with individuals without a metabolic comorbid condition, those with 1, 2 or ≥3 conditions had a 9% (1.09; 95% CI 1.00 to 1.17), 12% (1.12; 95% CI 1.01 to 1.24) and 31% (1.31; 95% CI 1.13 to 1.51) higher risk of early-onset CRC (ptrend <0.001). No associations were observed for one or two metabolic comorbid conditions and CRC diagnosed at age 50–64. These positive associations were driven by proximal (OR per condition 1.14; 95% CI 1.06 to 1.23) and distal colon cancer (OR 1.09; 95% CI 1.00 to 1.18), but not rectal cancer (OR 1.03; 95% CI 0.97 to 1.09). Conclusions: Metabolic dysregulation was associated with increased risk of early-onset CRC, driven by proximal and distal colon cancer, thus at least in part contribute to the rising incidence of early-onset CRC.